The human use of animals case studies in ethical choice - Orlans, F. Barbara (Oxford University Press, 1998)
"The first set of case studies on animal use, this volume offers a thorough, up-to-date exploration of the moral issues related to animal welfare. Its main purpose is to examine how far it is ethically justifiable to harm animals in order to benefit mankind. An excellent introduction provides a framework for the cases and sets the background of philosophical and moral concepts underlying the subject." "The Human Use of Animals will be welcomed by students and faculty in law, philosophy, ethics, public policy, religion, medicine, and veterinary medicine. It will also interest activists in the animal protection movement and members of animal protection organizations and Institutional Animal Care and Use Committees."--BOOK JACKET.